2016
DOI: 10.1371/journal.pone.0148304
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of QALY and DALY Use in Surgical Cost-Utility Analyses: A Systematic Review

Abstract: BackgroundSurgical interventions are being increasingly recognized as cost-effective global priorities, the utility of which are frequently measured using either quality-adjusted (QALY) or disability-adjusted (DALY) life years. The objectives of this study were to: (1) identify surgical cost-effectiveness studies that utilized a formulation of the QALY or DALY as a summary measure, (2) report on global patterns of QALY and DALY use in surgery and the income characteristics of the countries and/or regions invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 29 publications
(47 reference statements)
0
17
0
2
Order By: Relevance
“…We reported our outcomes in QALYs gained because 15D is validated for that purpose [ 8 ]. In a systematic review of global surgical cost-effectiveness analyses, QALYs were more common, though less so in low- or middle-income countries [ 20 ]. Though these comparator studies reported DALYs, theoretical comparisons between QALYs and DALYs can be made, and occasionally QALYs gained will be close to or equal DALYs averted [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We reported our outcomes in QALYs gained because 15D is validated for that purpose [ 8 ]. In a systematic review of global surgical cost-effectiveness analyses, QALYs were more common, though less so in low- or middle-income countries [ 20 ]. Though these comparator studies reported DALYs, theoretical comparisons between QALYs and DALYs can be made, and occasionally QALYs gained will be close to or equal DALYs averted [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, both the disability weight and the DALY have gained credence as important advocacy tools to highlight the burden and impact of disease at a population level. DALYs and quality‐adjusted life years have been used in 825 national studies to demonstrate that surgical interventions are cost‐effective global priorities . Disability weights have been used to estimate the potential global productivity loss associated with uncorrected refractive error, and with uncorrected presbyopia .…”
Section: Summary Of Studies Estimating a Disability Weight For Blindnessmentioning
confidence: 99%
“…DALYs and quality-adjusted life years have been used in 825 national studies to demonstrate that surgical interventions are costeffective global priorities. 18 Disability weights have been used to estimate the potential global productivity loss associated with uncorrected refractive error, 19 and with uncorrected presbyopia. 20 Multiple organizations advocate 'DALYs averted' as bottom-line performance metrics for guiding strategic and resource prioritization decisions in relation to competing public health interventions.…”
mentioning
confidence: 99%
“…Finally, thoroughly assessing the ultimate costs to society of these various reconstructive techniques would require assessments (such as qualityand disability-adjusted life years) that would incorporate long-term measures of disease burden normalized to the cost of treating the disease [7]. The road to obtaining meaningful and detailed long-term data on functional outcome, cost, and cost-effectiveness will be difficult, but is the only rational way to advance the surgical treatment of this rare but potentially devastating condition.…”
Section: How Do We Get There?mentioning
confidence: 99%